Factors Associated with Use of Intra-Uterine Device in Women of Reproductive Age in Boyolali, Central Java - Susilowati, Bekti; Wekadigunawan, CSP.; Murti, Bhisma; Rahardjo, Setyo (Journal of Maternal and Child Health, 2018)
Background: Family planning is a key strategy for reduction of maternal mortality. Family planning aims to control birth in order to control population growth. Long-acting reversible contraceptives (LARCs), which include intra-uterine device (IUD), are the most effective methods of birth control. Studies into factors affecting the uptake of IUD was lacking in Indonesia. This study aimed to investigate factors associated with use of IUD in women of reproductive age in Boyolali, Central Java, using multilevel analysis model and Theory of Planned Behavior. Subjects and Method: This was a case control study carried out in 25 posyandus (integrated community health posts) in Boyolali, Central Java, from April to June 2018. A sample of 200 women was selected by simple random sampling. The dependent variable was IUD use. The independent variables were education, family income, intention, attitude, subjective norm, perceived behaviour control, and husband support. The data were collected by questionnaire and analyzed by a multilevel logistic regression on Stata 13. Results: IUD use among women reproductive age increased with higher maternal education (b= 4.06; 95% CI= 0.68 to 7.44; p=0.019), higher family income (b= 3.90; 95% CI= 1.67to 7.64; p=0.041), positive attitude (b= 4.54; 95% CI= 0.52 to 8.55; p=0.027), positive subjective norm (b= 3.06; 95% CI= 0.01to 6.10; p= 0.049), strong perceived behaviour control (b= 3.40; 95% CI= -0.04to 6.85; p=0.053), strong intention (b= 3.18; 95% CI= -0.06to 6.41; p= 0.054), and strong husband support (b= 4.28; 95% CI= 0.01to 7.44; p= 0.050). Posyandu had a contextual effect on IUD use with ICC= 32.10%. Conclusion: IUD use among women reproductive age increases with higher maternal education, higher family income, positive attitude, positive subjective norm, strong perceived behaviour control, strong intention, and strong husband support. Posyandu has sizeable contextual effect on IUD use. Keywords: intra-uterine device, utilization, determinants, multilevel analysis Correspondence: